Comparison of Secret Splitting, Secret Sharing and Recursive Threshold Visual Cryptography for Security of Handwritten Images - Sugianto Sugianto; Suharjito Suharjito; Nico Surantha (Universitas Ahmad Dahlan, 2018)
The secret sharing is a method to protect confidentiality and integrity of the secret messages by distributing the message shares into several recipients. The secret message could not be revealed unless the recipients exchange and collect shares to reconstruct the actual message. Even though the attacker obtain shares shadow during the share exchange, it would be impossible for the attacker to understand the correct share. There are few algorithms have been developed for secret sharing, e.g. secret splitting, Asmuth-Bloom secret sharing protocol, visual cryptography, etc. There is an unanswered question in this research about which method provides best level of security and efficiency in securing message. In this paper, we evaluate the performance of three methods, i.e. secret splitting, secret sharing, and recursive threshold visual cryptography for handwritten image security in terms of execution time and mean squared error (MSE) simulation. Simulation results show the secret splitting algorithm produces the shortest time of execution. On the other hand, the MSE simulation result that the three methods can reconstruct the original image very well.